Features of the Criminal Legislation of Some Foreign Countries in the Protection of Persons from Sexually Transmitted Diseases and HIV Infection - Narzilloev Farhod Nasiloevich (Zien Journals, 2023)
The article presents the concepts of crimes related to the spread of sexually transmitted diseases or HIV infection (AIDS), their social danger as a global problem of the international level, legal characteristics, information about the norms established in the legislation of foreign countries to combat these crimes and their uniqueness.
Keywords: venereal disease; HIV infection; AIDS; social risk